Patient characteristics associated with treatment initiation and engagement among individuals diagnosed with alcohol and other drug use disorders in emergency department and primary care settings. Issue 3 (3rd July 2019) - Kline-Simon, Andrea H.; Stumbo, Scott P.; Campbell, Cynthia I.; Binswanger, Ingrid A.; Weisner, Constance; Haller, Irina V.; Hechter, Rulin C.; Ahmedani, Brian K.; Lapham, Gwen T.; Loree, Amy M.; Sterling, Stacy A.; Yarborough, Bobbi Jo H.
Abstract: Background : Treatment initiation and engagement rates for alcohol and other drug (AOD) use disorders differ depending on where the AOD use disorder was identified. Emergency department (ED) and primary care (PC) are 2 common settings where patients are identified; however, it is unknown whether characteristics of patients who initiate and engage in treatment differ between these settings. Methods: Patients identified with an AOD disorder in ED or PC settings were drawn from a larger study that examined Healthcare Effectiveness Data and Information Set (HEDIS) AOD treatment initiation and engagement measures across 7 health systems using electronic health record data ( n = 54, 321). Multivariable generalized linear models, with a logit link, clustered on health system, were used to model patient factors associated with initiation and engagement in treatment, between and within each setting. Results: Patients identified in the ED had higher odds of initiating treatment than those identified in PC (adjusted odds ratio [aOR] = 1.89, 95% confidence interval [CI] = 1.73–2.07), with no difference in engagement between the settings. Among those identified in the ED, compared with patients aged 18–29, older patients had higher odds of treatment initiation (age 30–49: aOR = 1.25, 95% CI = 1.12–1.40; age 50–64: aOR = 1.42, 95% CI = 1.26–1.60; age 65+: aOR = 1.27, 95% CI = 1.08–1.49). However, among those identified in PC, compared with patients aged 18–29, older patients were less likely to initiate (age 30–49: aOR = 0.81, 95% CI = 0.71–0.94; age 50–64: aOR = 0.68, 95% CI = 0.58–0.78; age 65+: aOR = 0.47, 95% CI = 0.40–0.56). Women identified in ED had lower odds of initiating treatment (aOR = 0.80, 95% CI = 0.72–0.88), whereas sex was not associated with treatment initiation in PC. In both settings, patients aged 65+ had lower odds of engaging compared with patients aged 18–29 (ED: aOR = 0.61, 95% CI = 0.38–0.98; PC: aOR = 0.42, 95% CI = 0.26–0.68). Conclusion: Initiation and engagement in treatment differed by sex and age depending on identification setting. This information could inform tailoring of future AOD interventions.